2016
DOI: 10.3892/mmr.2016.5022
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of ANXA1 suppresses the biological behavior of human NSCLC cells in vitro

Abstract: Annexin A1 (ANXA1) is a member of the annexin superfamily. Previous studies have reported that ANXA1 is highly expressed in various types of malignant tumor; however, its role in the progression of non-small cell lung cancer (NSCLC) remains to be fully clarified. The present study aimed to investigate the oncogenic role of ANXA1 in NSCLC cells in vitro. RNA interference was used to down-regulate ANXA1 expression in A549 and H1299 cells using a small interfering RNA lentiviral vector. Subsequently, cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…In colon and gastric cancers, ANXA1 interacts with formyl peptide receptors to promote cell migration and invasion (20,21). In non-small cell lung cancer, ANXA1 knockdown suppressed cell proliferation and metastasis (22). However, ANXA1 acts as a tumor suppressor by reducing cell proliferation and attenuating the metastatic potential in breast cancer (23).…”
Section: Introductionmentioning
confidence: 99%
“…In colon and gastric cancers, ANXA1 interacts with formyl peptide receptors to promote cell migration and invasion (20,21). In non-small cell lung cancer, ANXA1 knockdown suppressed cell proliferation and metastasis (22). However, ANXA1 acts as a tumor suppressor by reducing cell proliferation and attenuating the metastatic potential in breast cancer (23).…”
Section: Introductionmentioning
confidence: 99%
“…Data presented from our previous work showed that the expression of ANXA1 was significantly upregulated in eight matched cancer tissues and five NSCLC cell lines, compared with the normal tissues and cell lines . ANXA1 was detected at a higher expression level in the A549 cells than in human bronchial epithelial cells (16HBE).…”
Section: Resultsmentioning
confidence: 94%
“…The expression of ANXA1 has been reported to be reduced or increased in many types of cancer. We and others have recently reported that the expression of ANXA1 is upregulated in lung cancer . Of importance, ANXA1 has been shown to activate nuclear factor (NF)‐κB in T cells, and T cells from ANXA1‐deficient mice showed decreased NF‐κB activation, indicating that ANXA1 may somehow regulate NF‐κB .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanisms underlying ANXA1 modulation of cellular responses have not been fully determined. The previous study revealed that ANXA1 upregulation in lung cancer, and suppressing ANXA1 gene expression by the lentiviral vector LV-ANXA1-RNAi, may inhibit the proliferation, migration and invasion capabilities of lung cancer cells (31).…”
Section: Discussionmentioning
confidence: 99%